THE INFLUENCE OF CALCIFICATION AND NPK FERTILIZERS ON THE ECONOMICS OF TRITICALE PRODUCTION - Babić, Violeta; Rajičić, Vera; Terzić, Dragan; Dugalić, Marijana; Đurić, Nenad; Vučić, Marija (Economics of Agriculture, 2023)
The tests were performed on the property of the Agricultural and Chemical School “Doctor Djordje Radic” in Kraljevo, on pseudogley soil, during a two-year period (2015/16 and 2016/17). Based on the analysis of production value and total variable costs, a production calculation was made. Elements of economic efficiency (productivity, economy and profitability) were calculated for all four variants of fertilization. The tests showed a significant variation in grain yield in the tested fertilization variants. During the two-year research, the T2 variant fertilized with mineral nutrients with increased phosphorus dose (NP2K) had the most favorable values of economic efficiency indicators. Variant T2 can be considered the most profitable and most cost-effective, regardless of the fact that the yield and production value were the highest in variant T4, which is fertilized with a combination of mineral nutrients with increased doses of phosphorus, lime and organic fertilizers.